2022
DOI: 10.1021/acsami.2c11143
|View full text |Cite
|
Sign up to set email alerts
|

Direct Air Capture of CO2 Using Poly(ethyleneimine)-Functionalized Expanded Poly(tetrafluoroethylene)/Silica Composite Structured Sorbents

Abstract: The rapidly increasing atmospheric CO 2 concentration has driven research into the development of cost-and energy-efficient materials and processes for the direct air capture of CO 2 (DAC). Solid-supported amine materials can give high CO 2 uptakes and acceptable sorption kinetics, but they are generally prepared in powder forms that are likely not practically deployable in large-scale operations due to significant pressure drops associated with packed-bed gas−solid contactors. To this end, the development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 67 publications
(107 reference statements)
0
13
0
Order By: Relevance
“…Moreover, differences in surface chemistries in support materials can result in different binding motifs between the amine and the support, which also has the potential to influence the CO 2 capture performance. A variety of porous support materials have been used for amine impregnation, including silica, γ-alumina, MOFs, zeolite, and mixed metal oxides. , Despite this, the effects of amine-solid support interactions on CO 2 adsorption behavior are still poorly understood. Furthermore, most prior DAC studies are limited to adsorption temperatures above indoor ambient room temperature (>20 °C).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, differences in surface chemistries in support materials can result in different binding motifs between the amine and the support, which also has the potential to influence the CO 2 capture performance. A variety of porous support materials have been used for amine impregnation, including silica, γ-alumina, MOFs, zeolite, and mixed metal oxides. , Despite this, the effects of amine-solid support interactions on CO 2 adsorption behavior are still poorly understood. Furthermore, most prior DAC studies are limited to adsorption temperatures above indoor ambient room temperature (>20 °C).…”
Section: Introductionmentioning
confidence: 99%
“…37,38 However, it should be noted that the CO 2 capacity under humidity conditions is without exception much larger than the dry CO 2 capacity (2.53 mmol COd 2 /g adsorbent , not shown here), which is in line with the literature showing an enhancement in CO 2 capacity in the presence of water that originates from the improved stoichiometry from carbamates to bicarbonates. 39,40 The water capacity of 50TEPA/SBA-15 increases with RH and is about 2−5 times the CO 2 capacity at any given RH, which is rationalized not only by the hydrophilicity of amine-functionalized solid adsorbents 39 but also by the multilayer adsorption of H 2 O molecules. 41 Figure 5b presents the CO 2 capacity data of 50TEPA/SBA-15 in 10 adsorption−desorption cycles.…”
Section: Resultsmentioning
confidence: 98%
“…These sorbents showed potential for costeffective and energy-efficient DAC applications. 37 Researchers demonstrated the effectiveness of thin film composite membranes for CO 2 separation. These membranes, consisting of specific materials, showed super-permeable characteristics and outstanding CO 2 separation performance.…”
Section: Introductionmentioning
confidence: 99%
“…A study demonstrated DAC sorbents based on PEI‐functionalized ePTFE/silica composite materials for CO 2 capture. These sorbents showed potential for cost‐effective and energy‐efficient DAC applications 37 . Researchers demonstrated the effectiveness of thin film composite membranes for CO 2 separation.…”
Section: Introductionmentioning
confidence: 99%